Elevating Public Service: A Comprehensive Review of Public Service Motivation - Royhan, Muhammad (Jurnal Borneo Administrator, 2025)
The impact of digital change, public organization reform, and the COVID-19pandemic has brought many changes in public services worldwide. These conditions demand improvements in public service that exceed expectations. Public service motivation (PSM) is urgently needed for public sector managers to motivate employees with limited government resources. This article reviews the latest PSM literature, analyzing 210 articles selected using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol. All selected studies are categorized into five research areas: literature reviews, conceptual development, measurement advancements, PSM as an independent variable, and PSM as a dependent variable. The findings indicate that the evolution of PSM research presents opportunities for more focused literature reviews while emphasizing the need for empirical studies across various service sectors to address conceptual overlaps between PSM and related concepts. Furthermore, a multidisciplinary approach in developing antecedent and outcome variables, along with the adoption of more rigorous research designs, is essential for deepening the understanding of PSM. This study outlines a future research agenda and offers practical implications for policy formulation and the enhancement of public service effectiveness.